Factors Influencing Energy Intensity in Four Chinese Industries - Fisher-Vanden, Karen; Hu, Yong; Jefferson, Gary; Rock, Michael; Toman, Michael (World Bank, Washington, D.C., 2013)
Energy intensity has declined significantly in four Chinese industries -- pulp and paper; cement; iron and steel; and aluminum. While previous studies have identified technological change within an industry to be an important influence on energy intensity, few have examined how industry-specific policies and market factors also affect industry-level intensity. This paper employs unique firm-level data from China's most energy-intensive large and medium-size industrial enterprises in each of these four industries over a six-year period from 1999 to 2004. It empirically examines how China's energy-saving programs, liberalization of domestic markets, openness to the world economy, and other policies, contribute to the decline in energy intensity in these industries. The results suggest that rising energy costs are a significant contributor to the decline in energy intensity in all four industries. China's industrial policies targeting scale economies -- for example, "grasping the large, letting go off the small" -- also seem to have contributed to reductions in energy intensity in these four industries. However, the results also suggest that trade openness and technology development led to declines in energy intensity in only one or two of these industries. Finally, the analysis finds that energy intensities vary among firms with different ownership types and regional locations.